ANALYSIS OF THE EFFECT OF TOTAL MOISTURE (TM), ASH CONTENT (ASH), AND TOTAL SULFUR (TS) ON THE GROSS CALORIFIC VALUE OF COAL SEAM 16 AT PT UNGGUL NUSANTARA - Suratno Suratno; Stephani Sandan; Selma Ayu Andin (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the relationship and influence of coal quality parameters which include Total Moisture (TM), Ash Content (ASH), and Total Sulfur (TS) on Gross Calorific Value (GCV). The data used in this study is data from laboratory tests on 23 samples of Run Of Mine (ROM) coal at seam 16 at PT Unggul Nusantara, North Barito Regency, Central Kalimantan. Data analysis was performed statistically using the help of SPSS software through Pearson correlation test and multiple linear regression analysis. The results of the correlation test showed that simultaneously, the TM, ASH, and TS parameters had a very strong relationship with the GCV value with a correlation coefficient (R) of 0.893 and contributed an influence of 76.5%. Partially, Ash Content (ASH) had a very strong negative relationship (r = -0.881) and had a significant effect on calorie values (p = 0.000). Each 1% increase in ash content would decrease the GCV value by 68.249 Kcal/Kg. Meanwhile, Total Moisture had a significant positive relationship by simple correlation (r = 0.506, p = 0.014), but showed no partial significant effect in multiple regression models (p = 0.364). Total Sulfur was found to have a very weak negative relationship (r = -0.182) and had no significant effect on GCV values (p = 0.406). This study concludes that Ash Content is the most dominant parameter that affects the reduction of the caloric value of coal seam 16 at PT Unggul Nusantara.